2020
DOI: 10.1055/a-1120-8907
|View full text |Cite
|
Sign up to set email alerts
|

Bildgebung bei Uveitis

Abstract: ZusammenfassungBildgebende Verfahren sind Schlüsselelemente in der Diagnostik und Behandlung von Augenkrankheiten. Dies gilt insbesondere für intraokulare Entzündungen. In diesem Beitrag werden die aktuellen Bildgebungsmodalitäten wie optische Kohärenztomografie (OCT), OCT-Angiografie, Fluorescein- und Indocyaningrünangiografie, Fundusautofluoreszenz sowie Weitfeldbildgebungsmodalitäten erörtert. Der gezielte Einsatz dieser Untersuchungsmethoden wird abhängig vom Schwerpunkt der intraokularen Entzündung darges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Furthermore, combination of different non-invasive imaging methods (FAF modalities with different excitation wavelengths, OCT, CFP, infrared reflectance) for the monitoring of certain uveitis entities instead of recurrent invasive methods such as FA and ICG-A may be a useful alternative for routine clinical practice [66,74]. For example, in a case of chronic VKH syndrome, Vasconcelos-Santos et al suggested the combination of FAF and OCT as a non-invasive alternative to FA and ICG-A to delineate RPE/PR changes and follow the progression of the disease [45].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, combination of different non-invasive imaging methods (FAF modalities with different excitation wavelengths, OCT, CFP, infrared reflectance) for the monitoring of certain uveitis entities instead of recurrent invasive methods such as FA and ICG-A may be a useful alternative for routine clinical practice [66,74]. For example, in a case of chronic VKH syndrome, Vasconcelos-Santos et al suggested the combination of FAF and OCT as a non-invasive alternative to FA and ICG-A to delineate RPE/PR changes and follow the progression of the disease [45].…”
Section: Discussionmentioning
confidence: 99%